Determination of Consumer-Based Financial Brand Value in Banking Activities - Bağcı, Haşim; Uslu Divanoğlu, Sevilay (My University, 2022)
The banking sector, which has great market potential in Turkey, is developing rapidly in recent years. Along with such rapid development, competition also increases. Therefore, in order to differ from competitors and to excel in competition, banks should raise awareness of their services and render their brands attractive. From a customer perspective; both the financial brand value indicated by statistical data and the consumer-based brand value expressed by services are crucial. In this study, according to the potential customers of the banks in Aksaray; it was be tried to determine which bank has the highest financial brand value and the factors that affect the financial brand value of banks. Measures to be taken in order to increase the financial brand value and solution suggestions for the banks that are customer-oriented have been presented. Since it is difficult to reach all customers of the banks in Aksaray province, a group of 300 people selected impartially from the population was determined as the sample. The questionnaire was applied to 300 people by a simple random sampling method. It can be claimed that there is a significant relationship between the gender of the customers and the confidence felt in the bank, the choice of the bank in the context of monthly income and brand loyalty, and the time that consumers get service from the bank and their recognition of the symbol of the bank. It was concluded that the age range of consumers is effective in the awareness of the bank.